Analisis Risiko Operasional Jalan Tol Jagorawi PT Jasa Marga (Persero) Tbk - Satriaputri, Dwinapriyanti; Cahyadi, Eko Ruddy (Jurnal Manajemen dan Organisasi, 2015)
As one of the busiest toll roads in Indonesia, Jagorawi is exposed to various operational risks.  The purposes of this research are to analyze operational risks of Jagorawi toll road and to determine the effectiverisk reduction strategies. Cause and effect diagrams are employed to identify and classify these  risks. Then risk priorities are quantified by applying Failure Mode Effect Analysis (FMEA). Finally, in order to determine prioritized strategies, Analytical Hierarchy Process is applied. The results indicate that the main risk is the traffic risk. The most prioritized risk reduction strategies are educating both the toll road users and surrounding inhabitants. This is then needs to be followed by developing the instrastructure, investing human resource quality, automating gate, and improving the service and safety.Keywords : AHP, FMEA, cause-effect, operational risk, toll road